Environment Influences on the Emotion of Usher’s Friend in the Fall of the House of Usher - Santa Maya Pramusita (Journal of English Language Studies, 2018)
Nature is deeply powerful that it can give either bad or good influence toward human’s life. In this paper, the influence of nature toward the emotion of Usher’s friend as one of the characters in the story ‘The Fall of The House of Usher’ by Edgar Allan Poe is discussed. The main aim of this paper is to disclose how nature around the house or the environment is represented in the story and how its presence affect human’s emotion in the lens of ecocriticism. As for the methodology used in this research is qualitative-descriptive method in which the researcher read the story and some related references to gain deeper comprehension, after that critically analyze the story based on the theory of ecocriticism. From this analysis, the writer finds out the ecological imbalance in the environment of Usher’s house which is marked by the dead trees, dead lake, and poor quality of air. While the inner side of his house is just as bad. It is deeply dark and unkempt, making a lot of germs live in. Such thing indeed spreads bad influence to the emotion of Usher’s friend as the visitor in the house.